The Influence of the COVID-19 Pandemic on Mental Well-Being and Psychological Distress: Impact Upon a Single Country - Gray, Nicola S.; O'Connor, Chris; Knowles, James; Pink, Jennifer; Simkiss, Nicola J.; Williams, Stuart D.; Snowden, Robert J. (Frontiers in Psychiatry, 2020)
The COVID-19 pandemic is likely to have affected the psychological wellbeing and mental health of many people. Data on prevalence rates of mental health problems are needed for mental health service planning. We examined psychological wellbeing and prevalence of clinically significant mental distress in a large sample from Wales 11-16 weeks into lockdown, and compared this to population-based data collected pre-COVID-19. Data were collected using an online survey disseminated across Wales and open to adults (age 16+) from 9 June to 13 July 2020. Psychological wellbeing was indexed via the Warwick-Edinburgh Mental Wellbeing Scale, and psychological distress was indexed via the K10. Data were compared to those from April 2018-March 2019 gathered by the National Survey for Wales. Data from 12,989 people were analysed. Wellbeing showed a large decrease from pre-COVID levels. Clinically significant psychological distress was found in around 50% of the population (men = 47·4%, women = 58·6%), with around 20% showing “severe” effects (men = 17·0%, women = 20·9%): a 3-4-fold increase in prevalence. Most affected were young people, women, and those in deprived areas. By June-July 2020 the COVID-19 pandemic had dramatic effects on the mental health of people living in Wales (and by implication those in the UK and beyond). The effects are larger than previous reports. This probably reflects that the current data were taken deeper into the lockdown period than previous evaluations. Mental health services need to prepare for this wave of mental health problems with emphasis on younger adults, women, and in areas of greater deprivation.